2017
DOI: 10.1002/2017gl074895
|View full text |Cite
|
Sign up to set email alerts
|

Dayside response of the magnetosphere to a small shock compression: Van Allen Probes, Magnetospheric MultiScale, and GOES‐13

Abstract: Observations from Magnetospheric MultiScale (~8 Re ) and Van Allen Probes (~5 and 4 Re ) show that the initial dayside response to a small interplanetary shock is a double‐peaked dawnward electric field, which is distinctly different from the usual bipolar (dawnward and then duskward) signature reported for large shocks. The associated E × B flow is radially inward. The shock compressed the magnetopause to inside 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 57 publications
(74 reference statements)
5
19
0
Order By: Relevance
“…The statistics in Liu et al [2017] also showed that the dynamic pressures of the IP shocks associated with dropout echo events are usually modest. As well, the radial propagation speed of the pulse v 0 = 1,000 km/s and the averaged azimuthal propagation speed of the pulse 691 km/s at L = 6.6 in our study are consistent with the propagation velocity ranged from about 600 to 1,300 km/s obtained in previous observations (Cattell et al, 2017;Foster et al, 2015;Schmidt & Pedersen, 1988;Takahashi et al, 2017;Zong et al, 2009). As well, the radial propagation speed of the pulse v 0 = 1,000 km/s and the averaged azimuthal propagation speed of the pulse 691 km/s at L = 6.6 in our study are consistent with the propagation velocity ranged from about 600 to 1,300 km/s obtained in previous observations (Cattell et al, 2017;Foster et al, 2015;Schmidt & Pedersen, 1988;Takahashi et al, 2017;Zong et al, 2009).…”
Section: The Shock-induced Magnetosonic Pulsesupporting
confidence: 93%
See 1 more Smart Citation
“…The statistics in Liu et al [2017] also showed that the dynamic pressures of the IP shocks associated with dropout echo events are usually modest. As well, the radial propagation speed of the pulse v 0 = 1,000 km/s and the averaged azimuthal propagation speed of the pulse 691 km/s at L = 6.6 in our study are consistent with the propagation velocity ranged from about 600 to 1,300 km/s obtained in previous observations (Cattell et al, 2017;Foster et al, 2015;Schmidt & Pedersen, 1988;Takahashi et al, 2017;Zong et al, 2009). As well, the radial propagation speed of the pulse v 0 = 1,000 km/s and the averaged azimuthal propagation speed of the pulse 691 km/s at L = 6.6 in our study are consistent with the propagation velocity ranged from about 600 to 1,300 km/s obtained in previous observations (Cattell et al, 2017;Foster et al, 2015;Schmidt & Pedersen, 1988;Takahashi et al, 2017;Zong et al, 2009).…”
Section: The Shock-induced Magnetosonic Pulsesupporting
confidence: 93%
“…In fact, various studies have indicated that the response of magnetosphere to an IP shock could be characterized by the propagating magnetosonic pulse. The observations on the profile and propagation of the sudden impulse induced by IP shocks also confirm the picture of the propagating magnetosonic pulse (e.g., Cattell et al, 2017;Schmidt & Pedersen, 1988;Shinbori et al, 2004;Takahashi et al, 2017;Zhang et al, 2018). Further, global magnetohydrodynamics (MHD) simulations showed the propagation of the shock-induced magnetosonic pulse through the whole magnetosphere (e.g., Guo et al, 2005;Ridley et al, 2006;Samsonov et al, 2007).…”
Section: The Shock-induced Magnetosonic Pulsesupporting
confidence: 66%
“…This effect has been used to explain the dispersionless injections during substorms with a decelerating impulse (e.g., Li et al, 1998;Sarris et al, 2002). However, this effect could be negligible for IPS-induced electric field impulses, as the V E × B caused by the impulsive electric field, calculated above to be below 100 km/s, is much smaller than the propagation speed of the impulse, which is about 600 to 1,100 km/s corresponding to local fast magnetosonic wave speed estimates (e.g., Cattell et al, 2017;Foster et al, 2015;Schmidt & Pedersen, 1987;Takahashi et al, 2017). The second mechanism involves electrons with the right energy that can follow a propagating impulse while drifting azimuthally.…”
Section: 1029/2018gl078809mentioning
confidence: 98%
“…Cattell et al () documented the impact of the modest interplanetary shock that was observed upstream of Earth by ACE at 1231 UT and by Wind at 1241 UT. The shock compressed the dayside magnetopause to inside 8 R E .…”
Section: Satellite Observationsmentioning
confidence: 99%